2004
DOI: 10.1097/00002030-200410210-00008
|View full text |Cite
|
Sign up to set email alerts
|

Survival in patients with HIV infection and viral hepatitis B or C

Abstract: Patients with HIV and viral hepatitis had greater liver mortality than patients with HIV alone, but had comparable HIV mortality. Co-infection with hepatitis B is associated with hepatic outcomes similar to hepatitis C. Control of immunosuppression with HAART and CD4 counts > 200 x 10(6) cells/l are associated with better hepatic outcomes and should be the first priority in patients with HIV and viral hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
163
0
9

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(191 citation statements)
references
References 21 publications
14
163
0
9
Order By: Relevance
“…25 The impact of immunosuppression on liver mortality is one reason for this recommendation. [2][3][4][5] In the present study, lack of control of HIV replication was a risk factor for progression. This is an additional reason to consider earlier ART initiation.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…25 The impact of immunosuppression on liver mortality is one reason for this recommendation. [2][3][4][5] In the present study, lack of control of HIV replication was a risk factor for progression. This is an additional reason to consider earlier ART initiation.…”
Section: Discussionmentioning
confidence: 49%
“…1 Low CD4 cell counts, lack of exposure to antiretroviral therapy (ART), and advanced liver disease are risk factors for liver events and mortality in cohort studies. [1][2][3][4][5] Particularly, CD4 cell recovery and suppression of HIV replication after starting highly active antiretroviral therapy (HAART) are predictors of survival free of complications of cirrhosis. 5 Most data on liver fibrosis progression in HIV and HCV coinfection come from cross-sectional studies that relied on a single liver biopsy.…”
mentioning
confidence: 99%
“…The levels of HBV replication are increased in HIV-infected patients. A more rapid progression of liver fibrosis and a higher rate of hepatic decompensation on cirrhosis (but not HCC) have been demonstrated in concurrently infected patients [25,26]. The risk of HBV-associated end-stage liver disease and liver-related mortality may be increased in HIV concurrent infection [26,27].…”
Section: Hbv and Hdvmentioning
confidence: 99%
“…HIV increases the risk of cirrhosis and end-stage liver disease in HBV coinfection [36]. In some studies, the risk of liver related mortality has been found to be 2-3 times higher in HIV/HBV co-infected patients than in HIV-mono-infected patients [37]. HIV co-infection with HBV is associated with more frequent flares of hepatic transaminases, which can occur with immune reconstitution inflammatory syndrome (IRIS) owing to ART, interruption of HIV/HBV treatment, or the development of resistance to HIV/HBV treatment.…”
Section: Hiv/hbv Co-infectionmentioning
confidence: 99%